Analisis Semiotika Pesan Moral dan Nilai Sosial pada Iklan Cegah Stunting Itu Penting dengan Pendekatan Kualitatif - Fito Herlambang; Lathifa Prima Ghanisyana; Ghefira Prisyilia Azzahra; Fitria, Fitria (Yayasan Literasi Sains Indonesia, 2025)
This study uses Roland Barthes' semiotic technique to examine the social values and moral messages in the public service announcement